Low Light Availability Alters Root Exudation and Reduces Putative Beneficial Microorganisms in Seagrass Roots - Martin, Belinda C.; Gleeson, Deirdre; Statton, John; Siebers, Andre R.; Grierson, Pauline; Ryan, Megan H.; Kendrick, Gary A. (Frontiers in Microbiology, 2018)
Seagrass roots host a diverse microbiome that is critical for plant growth and health. Composition of microbial communities can be regulated in part by root exudates, but the specifics of these interactions in seagrass rhizospheres are still largely unknown. As light availability controls primary productivity, reduced light may impact root exudation and consequently the composition of the root microbiome. Hence, we analyzed the influence of light availability on root exudation and community structure of the root microbiome of three co-occurring seagrass species, Halophila ovalis, Halodule uninervis and Cymodocea serrulata. Plants were grown under four light treatments in mesocosms for two weeks; control (100 % surface irradiance (SI), medium (40 % SI), low (20 % SI) and fluctuating light (10 days 20 % and 4 days 100%). 16S rDNA amplicon sequencing revealed that microbial diversity, composition and predicted function were strongly influenced by the presence of seagrass roots, such that root microbiomes were unique to each seagrass species. Reduced light availability altered seagrass root exudation, as characterized using fluorescence spectroscopy, and altered the composition of seagrass root microbiomes with a reduction in abundance of potentially beneficial microorganisms. Overall, this study highlights the potential for above-ground light reduction to invoke a cascade of changes from alterations in root exudation to a reduction in putative beneficial microorganisms and, ultimately, confirms the importance of the seagrass root environment – a critical, but often overlooked space.